Study of linear mechanical stress on micro-satellite wire HARNESS - Ho, Jared Shao Rui (Nanyang Technological University, 2024)
This study examines and optimizes the impact of linear mechanical stress on microsatellite wire harnesses, which are essential components of satellite systems responsible for reliable power distribution and data transmission. The research is driven by the growing complexity of Very Low Earth Orbit satellites and their harsh operating environments. It investigates the challenges associated with the intricate design and assembly procedures, environmental stresses, and rigorous industry standards governing wire harnesses. This study evaluates critical factors such as material selection, harness routing, weight minimization, bending radius, and assembly techniques. It employs advanced methodologies, encompassing computational modelling, simulation, and iterative prototyping, to optimize the harness's performance and reliability. Additionally, the research applies innovative solutions, including structured problem-solving frameworks, to address design inefficiencies and enhance cross-functional collaboration. The study's findings inform the creation of wire harness systems that are lightweight, resilient, and optimized for performance, all while adhering to space industry standards. These insights hold important implications for the success of future satellite missions, bolstering operational capabilities and propelling advancements in space exploration.